Sistem Monitoring Menggunakan The Dude Sebagai Peningkatan Layanan Jaringan Komputer - Noor Muhammad Ayyub; Dimas Sasongko; Nuryanto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
One of the network monitoring methods is to use the dude software. In 2022, the Temanggung Regency Government through the Communication and Informatics Department of the Temanggung Regency which facilitates OPD, District, Kelurahan, Village, several UPT and schools. To increase service quality for all clients, so network monitoring development is needed uses the dude application software to carry out network monitoring which was previously only through the Whatsapp group. The development model that will be applied in this research is NDLC (Network Development Life Cycle). The research location was in Temanggung Regency in April 2023. The population in this study were five repeaters with different IPs, namely the Regional Secretariat, Dinkominfo, RSUD, SDN 2 Katekan, and Tlogopucang Village. The dude server has been installed on core router in data center that connected with whole networks. So all events and activities can be managed efficiently.